By the use of information technology in physical education students - Кашуба, В. О.; Футорний, С. М.; Голованова, Н. Л. (Slobozhanskyi Herald of Science and Sport, 2011)
Article is devoted to the use of information technology in physical education students. Currently, the system of values, motivations, habits, goal-directed behavior of an individual becoming a kind of kernel implementation of a social ideology in the formation of a physical fitness. In this context, one of the principal moments of a distribution to students knowledge about the importance of a physical fitness, the possibilities of using technology and conservation of corrective health through the use of information technology. In this process, one of the areas of information in modern society is the computerization of the process of physical education students.